Guillain-Barré syndrome. Issue 10280 (27th March 2021) - Shahrizaila, Nortina; Lehmann, Helmar C; Kuwabara, Satoshi
Summary: Guillain-Barré syndrome is the most common cause of acute flaccid paralysis worldwide. Most patients present with an antecedent illness, most commonly upper respiratory tract infection, before the onset of progressive motor weakness. Several microorganisms have been associated with Guillain-Barré syndrome, most notably Campylobacter jejuni, Zika virus, and in 2020, the severe acute respiratory syndrome coronavirus 2. In C jejuni -related Guillain-Barré syndrome, there is good evidence to support an autoantibody-mediated immune process that is triggered by molecular mimicry between structural components of peripheral nerves and the microorganism. Making a diagnosis of so-called classical Guillain-Barré syndrome is straightforward; however, the existing diagnostic criteria have limitations and can result in some variants of the syndrome being missed. Most patients with Guillain-Barré syndrome do well with immunotherapy, but a substantial proportion are left with disability, and death can occur. Results from the International Guillain-Barré Syndrome Outcome Study suggest that geographical variations exist in Guillain-Barré syndrome, including insufficient access to immunotherapy in low-income countries. There is a need to provide improved access to treatment for all patients with Guillain-Barré syndrome, and to develop effective disease-modifying therapies that can limit the extent of nerve injury. Clinical trials are currently underway to investigate some of the potential therapeutic candidates, including complement inhibitors, which, together with emerging data from large international collaborative studies on the syndrome, will contribute substantially to understanding the many facets of this disease.